Preparation of Ring-Methoxylated Arylnitromethanes by the Victor Meyer Reaction - Maksimenko, Anna S.; Buikin, Petr A.; Daeva, Elena D.; Kislyi, Victor P.; Semenov, Victor V. (Synthesis, 2022)
Easily accessible and stable ring-methoxylated benzyl chlorides react with AgNO2 to give mixtures of the corresponding arylnitromethanes and nitrite esters. A modified approach for the isolation of arylnitromethanes is described, which represents a valuable improvement of the established Victor Meyer reaction. The isolation technique, which involves reaction of the nitrite ester with urea in methanol, allows the desired arylnitromethanes to be isolated, without loss, in 29–75% yields, and generates the corresponding recyclable benzyl alcohols. Unexpectedly, ring-methoxylated benzyl iodides cannot be used because they are not sufficiently stable and produce tars under the developed reaction conditions.
Keywords: arylnitromethanes; benzyl chloride; polymethoxybenzene; nucleophilic substitution; Victor Meyer reaction